ChemInform Abstract: Amino Acid Chirons: A Tool for Asymmetric Synthesis of Heterocycles. Issue 39 (23rd September 2014) - Singh, Priyanka; Samanta, Krishnananda; Das, Sanjit Kumar; Panda, Gautam
Abstract Review: 146 refs.